Effects of interpregnancy interval and outcome of preceding pregnancy on present pregnancy outcome - Soni, Sona; Singh, Bharti; Agarwal, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of the present study was to estimate the effects of interpregnancy interval and outcome of preceding pregnancy on present pregnancy outcome. Methods: This study was undertaken as observational study. 1000 women were included in this study then interpregnancy interval categorized in 4 groups. Outcome of preceding pregnancy were included in term of induce abortion, miscarriage, still birth and live birth. Results: For each group the highest rate of IA occur for woman whose previous pregnancy ended with an IA. For pregnancy after an IA the rate of subsequent IA is 16.6%, 11.6%, 5% for IPI of <6 month, 6-14 months and 27-50 months respectively. Overall lowest rate of IA found for IPI of 27-50 months following live birth i.e. 1.25% and for group III 2% only. Rate of miscarriage was higher for IPI of <26 months began with a miscarriage 15.6% and 13.6% for following live birth. Conclusions: Outcome of present pregnancy not only depend upon interpregnancy interval but also depend upon outcome of preceding pregnancy. So, outcome of previous pregnancy will also determine outcome of present pregnancy.